Логістика в інфокомунікаційних системах - Бондаренко, B. C. (ХНУРЕ, 2023)
Logistics in infocommunication systems is a complex and critical aspect of modem business operations. As the world becomes increasingly connected and digitized, the management of logistics in the infocommunication industry is becoming more challenging. With so many factors at play, including supply chain management, inventory control, shipping and delivery, and customer service, businesses operating in the infocommunication industry must be strategic and efficient in their logistics management to remain competitive. Artificial intelligence (AI) can help automate routine tasks in logistics, improving efficiency and reducing errors.